Effects of multicomponent mixture "Solodok super" on the quality of wheat bread enriched with a sprouted grain mixture - Bilyk, Olena; Burchenko, Liudmila; Bondarenko, Yuliia; Piddubnyi, Volodymyr (My University, 2021)
This paper is dedicated to improving the technology of bakery products made from wheat flour with added mixture of sprouted grains. The sprouted grain mixture (SGM) contains wheat, barley, corn, and oat grains, produced by “Choice” LLC (Kyiv, Ukraine). It has been proven that increasing the amount of grain mixture to 15% to weight of flour has a negative impact on sensory, physical, and chemical qualities of bread products. This amount of sprouted grain mixture reduces viscosity and increases spreading of dough, which leads to the smaller volume of the finished products. Thus when adding 15% of the mixture, it is recommended to use multicomponent mixtures. Multicomponent mixture "Solodok SUPER" has been developed and its optimal dosage has been established. Using it increases specific volume of bread products and improves their porosity and shape stability.
Keywords: sprouted grain mixture; baking properties; consumer properties; wheat bread; bread freshness; bread enrichment; bread staling; кафедра технології хлібопекарських і кондитерських виробів